Analysis of molecular weight and structural changes in water-extractable arabinoxylans during the breadmaking process. (30th August 2022) - Nishitsuji, Yasuyuki; Whitney, Kristin; Nakamura, Kenji; Hayakawa, Katsuyuki; Simsek, Senay
Graphical abstract: Highlights: Breadmaking process impacts molecular weight of water extractable arabinoxylan. Diversity of water extractable arabinoxylan increased during breadmaking process. High molecular weight arabinoxylan shows major changes during breadmaking process. Xylose substitution was altered for arabinoxylan fractions during different stages. Water holding capacity of arabinoxylan changed due to molecular changes. Abstract: Arabinoxylans are important for dough and breadmaking properties. It is not clear how arabinoxylans of different molecular weights behave during the breadmaking process as well as the changes in individual structures. We investigated changes in the molecular weight and structure of water-extractable arabinoxylans. It was revealed that molecules larger than high molecular weight arabinoxylans were formed during the mixing and 1st fermentation (105 min before 1st punch). High molecular weight arabinoxylan continued to be degraded from mixing to the proofing stage. The arabinose to xylose ratio increased at mixing and the 1st fermentation due to solubilization of highly substituted arabinoxylan. Low molecular weight arabinoxylan did not show degradation and structural changes during the fermentation process, whereas the weight average molecular weight of low molecular weight arabinoxylan significantly decreased (P < 0.05) at mixing. Water extractable arabinoxylan shows different behaviors for molecular weight and structural changes during the breadmaking process.